Factors affecting the selection of an inhaler device for COPD and the ideal device for different patient profiles. Results of EPOCA Delphi consensus. (February 2018) - Miravitlles, Marc; Soler-Cataluña, Juan José; Alcázar, Bernardino; Viejo, José Luis; García-Río, Francisco
Abstract: Background: This study aimed to identify the relevant factors for the choice of an inhaler device by physicians and the selection of the most important characteristics of a device according to different characteristics of patients with COPD. Method: In this two-round Delphi survey, 96 Spanish COPD-expert pulmonologists completed an internet-based, self-administered questionnaire, which consisted of a first part with 19 items related to the prioritization of the drug or the device, the experience, ability and preference of the patient, and the experience and preferences of the healthcare professional. For each item, responses were grouped into three categories based on a 9-point Likert-type scale, calculating the response frequency and the degree of consensus. The second part included 18 items related to the inhalation devices with the aim to identify the main characteristics of a device for 8 different profiles of patients with COPD. Results: Experts considered that the selection of a device was relevant when choosing the treatment for COPD patients, although 62.5% of them prioritised the selection of the drug over the device. The experience of the patient (89.6%) and his/her ability to handle the device (97.9%), together with coordination (96.9%), ability to learn (87.5%) and adherence to therapy (84.4%) were the main aspects considered in the selection of inhalation device. The panel identified Respimat ® as the most adequate device for patients with either low inspiratory flow or severely impaired lung function and Spiromax ® for patients with either impaired fine motor skills or older than 70 years. Conclusions: Selection of the inhalation device is recognized by specialists as a strategic therapeutic decision and should be based on the characteristics of the individual patient. Some devices may be more adequate for different patient profiles.